GEOCHEMICAL STUDY OF SOURCE ROCKS AND OIL CHARACTERIZATION AT NORTH AMAN SUB-BASIN FIELD, CENTRAL SUMATRA BASIN - Moh Ganjar G, Reza
North Aman Sub-basin is an active field of PT CPI, to increase production and possibility of new petroleum system as a background then geochemical study and oil characterization analysis do to determine the characterization of rocks which have ability to be a good source rocks in the research area, to determine oil characterization, oil grouping and source rocks to oil correlation. Processing data will is oil condensate samples with bulk properties and moleculer properties. Data sorting of oil samples will focused at biomarker moleculer availability, an oil samples will tested based on normal alkana, sterana data and carbon isotop availability. Biomarker data which used in this study bound at sterana mass ion and triterpana. Sediment rocks samples from exploration well used to analized TOC, rock-eval pyrolysis and vitrinite reflectance. The geological and geophycical datas used for analysis about geological condition of research area correlate with the result of geochemical analsyis. Data input about top formation, thickness formation and temperature will be processed with PetroMod 1D software. Source rocks evaluation covered into source rocks potential, organic material type and maturity, analysis processed at five exploration well, namely: SR-CAN, SRKEL, SR-GUL, SR-PET and SR-SID. An oil characterization processed at ten production well, namely: P1 well Duri Formatin, D1 well Bangko Formation, D2 well Menggala Formation, V1 well Bangko Formation, R1 well Bekasap Formation, U1 and U2 well Upper Sihapas Formation, Q1 well Bekasap Formation, Q2 well Duri Formation and S1 well Menggala Formation. A good formation for source rock beside Brown Shale Formation is Lower Red Bed Formation, it is proved from the result of analysis showing that formation has good parameters in potential, organic material type and maturity. An oil characterization analysis with depositional enviroment with sterana distribution showing that one of an oil samples which is Q2 was derived from Lower Red Bed Formation. Hydrocarbon migration path controlled by geological structure feature like fault, and reservoar trap is also controlled by geological structure like anticline from inversion mechanism. Burial history and thermal gradient analysis at SR-SID well showing that source rock maturity start with Brown Shale Formation at Paleogene in 1700 meters depth and maximum maturity at Neogen in 2600 meters depth.